Kejadian Gangguan Kulit pada Petugas Sampah di Indonesia dan Faktor yang Mempengaruhinya: Studi Meta-Analisis Tahun 2016-2021 - Alvina Amanta Yudha; R. Azizah (Media Gizi Kesmas, 2023)
Background: Garbage can harm health if it is not managed properly. One of the health problems that can arise is skin disorders that often occur in workers in landfills due to a work environment that is not conducive and dirty. Objectives: The purpose of this study was to analyze the characteristic risk factors, personal hygiene, and use of personal protective equipment with the incidence of skin disorders in waste officers in Indonesia. Methods: This study used a meta-analysis method with a cross-sectional research design. The sample used was 24 research articles and data processing using JASP version 0.14.1 and then data analysis was carried out. Discussions: The results showed that the characteristics of the waste officer in the older age group variable had a risk of 1,116 times greater, the variable for the longer working hours group had a greater risk of 1,197, and the variable with a longer working year had a risk of 1,138 times greater to experience skin disorders. The personal hygiene behavior factor of the waste officer who is not good has a 1,648 times greater risk of experiencing skin disorders. The factor of using PPE for waste officers who are not good has a risk of 1,433 times greater for experiencing skin disorders. Conclusions: The highest risk factor in this study is the personal hygiene variable and the use of PPE to prevent and minimize the occurrence of skin disorders in waste officers, efforts can be increased in realizing good personal hygiene behavior and also wearing complete PPE.